Detection of In Vivo Mutation in the Hprt and Pig-a Genes of Rat Lymphocytes - Dobrovolsky, Vasily N; Shaddock, Joseph G; Mittelstaedt, Roberta A; Miura, Daishiro; Heflich, Robert H (Methods in molecular biology (Clifton, N.J.), 2019)
Assays for in vivo mutation are used to identify genotoxic hazards and phenotypes prone to genomic instability and cancer. The hypoxanthine guanine phosphoribosyl transferase (Hprt) gene and the phosphatidyl inositol glycan, class A (Pig-a) gene are endogenous X-linked genes that can be used as reporters of mutation in peripheral blood lymphocytes from most mammals. Here we describe methodology for measuring Hprt and Pig-a mutation in rat T-lymphocytes. The identification and selective expansion of mutant lymphocytes is based upon the phenotypic properties of Hprt- and Pig-a-deficient cells, that is, resistance to the purine analog, 6-thioguanine, or to the bacterial toxin, proaerolysin. Expanded mutants can be further analyzed by sequencing cDNA from the target transcripts for identification of small sequence alterations and by multiplex PCR analysis of genomic DNA for the detection of deletions.